2004
DOI: 10.1001/archopht.122.2.258
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Apolipoprotein E Gene Polymorphisms in Primary Open-angleGlaucoma

Abstract: To test the hypothesis that genetic polymorphisms of the apolipoprotein E (APOE) gene are associated with primary open-angle glaucoma (POAG), based on the association between neurodegenerative diseases and the APOE genotype. Methods: Genomic DNA was examined from an unrelated cohort of 137 POAG patients and 75 control subjects from the ophthalmology department of the Royal Victoria Infirmary. The APOE allele frequency (⑀2, ⑀3, and ⑀4 alleles) was studied by polymerase chain reaction amplification of the relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 22 publications
0
25
1
1
Order By: Relevance
“…31 The conflicting findings may be attributed to ethnic differences in the frequencies of APOE genotypes. The e4 allele frequencies in normal Caucasian study subjects have been reported to be 11.8 to 23.4%, 31,32,34,35 In Chinese, the APOE e4 allele occurs less frequently, ranging from 6.7%, 17 , 7.5%, 23 to 9.2% in the present study. It is also possible that a nearby gene with LD to APOE is the causative gene to NTG.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…31 The conflicting findings may be attributed to ethnic differences in the frequencies of APOE genotypes. The e4 allele frequencies in normal Caucasian study subjects have been reported to be 11.8 to 23.4%, 31,32,34,35 In Chinese, the APOE e4 allele occurs less frequently, ranging from 6.7%, 17 , 7.5%, 23 to 9.2% in the present study. It is also possible that a nearby gene with LD to APOE is the causative gene to NTG.…”
Section: Discussioncontrasting
confidence: 43%
“…32 However, a number of recent studies suggested the APOE polymorphisms in the promoter 33 and exon 4 are not risk factors of glaucoma. 34,35 All studies to date on associations of APOE with POAG were carried out in Caucasians. Taken together, the role of APOE in POAG is largely controversial.…”
mentioning
confidence: 99%
“…The APOEε 3 and APOEε 4 (Vickers et al 2002) alleles are associated with elevated risk for glaucomatous changes. However, two studies on Caucasian patients did not reveal an association between the APOEε 2/ε 3/ε 4 genotype and POAG (Ressiniotis et al 2004) or NTG (Lake et al 2004).…”
Section: Other Glaucoma Associated Genesmentioning
confidence: 93%
“…27 Nevertheless, in the English population there is contrasting data in which no significant association between the APOE "2 and "4 alleles and open angle glaucoma was detected. 28 As shown above, there are controversial results and could not claim whether APOE alleles constitute a risk factor or are protective against glaucoma. This discrepancy might be generated by higher exposure of populations to various environmental factors or different genetic backgrounds.…”
Section: Discussionmentioning
confidence: 99%